H-PVDF/MoS2 loose nanofiltration membranes prepared by 2D lamellar structure for efficient dye desalination - Shuoqing Shi; Jiajie Liu; Rui Liu; Liming Dong; Suping Yu (Journal of Water Process Engineering, 2026)

The deactivation and regeneration mechanisms of spent ceramic filter catalysts - Haowen Zheng; Changming Li; Quanlong Li; Shihao Li; Xiaocong Zhao; Liming Huang; Xing Huang; Chuanqiang Zhu; Jian Yu (Journal of Environmental Chemical Engineering, 2026)

Cold atmospheric plasma-modified multifunctional nanoemulsion co-delivering curcumin and resveratrol: Construction and application in tilapia preservation - Fazhu Li; Tingting Yang; Guanghua Xia; Zhongyuan Liu; Dawei Yu; Zhidong Liu; Liming Zhang; Jiamei Wang (Food Research International, 2026)

Effects of atmospheric cold plasma voltage on the interfacial properties of soy protein isolate-sodium alginate nanoemulsions co-loaded with curcumin and resveratrol and their application in surimi gels during chilled storage - Huiru Mo; Tingting Yang; Zhongyuan Liu; Guanghua Xia; Dawei Yu; Zhidong Liu; Yixiang Wang; Liming Zhang; Jiamei Wang (Food Research International, 2026)

Optimizing rice yield simulation by integrating dynamic dry matter partitioning and high-temperature stress with a remote sensing-based process model - Zhiyuan Ma; Jiahua Zhang; Liming Yu; Xin Jiang; Yun Bai; Shanshan Yang; Sha Zhang; Fengmei Yao (Field Crops Research, 2026)

Inverse identification of wind turbine horizontal thrust on steel-concrete hybrid tower using intelligent algorithm - Shou-Zhen Li; Yu-Hang Wang; Jinjin Wang; Ran Deng; Chao Hu; Liming Jiang (Engineering Structures, 2026)

Cell cycle reprogramming in plant symbiotic and pathogenic interactions - Haoran Guo; Liming Zhai; Nan Yu; Ertao Wang (Current Opinion in Plant Biology, 2026)

Genetic structure and diversity of four Chinese fir breeding populations over 60 years - Qihang Feng; Zhi-Qiang Chen; Benwen Zhao; Long Zhang; Shunde Su; Xie Zhang; Yu Chen; Yousry A. El-Kassaby; Harry X. Wu; Liming Bian (Tree Genetics & Genomes, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

Applications of surface-enhanced Raman scattering-based immunoassays in food hazards - Wei Xu; Gan Zhang; Wanglong Yu; Xiaoyue Xiao; Juan Peng; Liming Hu; Weihua Lai (Food Bioscience, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

The impact of cumulative obesity and genetic susceptibility on biological aging in Chinese older adults - Jiening Yu; Liming Zhang; Zhenqing Yang; Xueqing Jia; Ciyun Zhao; Jiaxin Liu; Jingyun Zhang; Xingqi Cao; Yinyi Song; Lu Li; Xuehui Sun; Hui Zhang; et al. (GeroScience, 2026)

Effect of Guide Vane Case on Hydrodynamic Performance and Unsteady Pressure-Pulsation Characteristics of Shaftless Pump-Jet Thruster - Taofeng Wang; Sanming Song; Liming Li; Jinxing Yu; Kaizhou Liu; Adam Rushworth; Xisheng Feng (Journal of Marine Science and Engineering, 2026)
Propulsors are essential power units for underwater vehicles and major sources of self-noise, with unsteady pressure pulsations linked to flow-induced noise. To study the impact of guide vane case on the hydrodynamic performance and pressure pulsation of a shaftless pump-jet thruster, six guide vane configurations were first compared under a reference operating condition of 600 rpm: a vaneless baseline, fixed vertical guide vanes, fixed forward-inclined guide vanes, fixed reverse-inclined guide vanes, co-rotating guide vanes, and counter-rotating guide vanes. Based on this comparison, the vertical-vane and counter-rotating-vane configurations were selected for extended operating-condition analysis under three rotational speeds and three inflow conditions. Transient numerical simulations were conducted using the SST k−ω turbulence model. The rotating regions were defined in a rotating reference frame, and the unsteady rotor–stator interaction was resolved using a transient sliding-mesh interface. Results show that the counter-rotating guide vane configuration achieves the highest head and efficiency among the tested cases, with a head of 1.8955 m and efficiency of 0.7306, representing increases of 19.64% and 22.87% over the fixed vertical guide vane case. The fixed forward-inclined guide vane exhibits the strongest thrust fluctuation and pressure pulsation. Pressure-pulsation intensity generally decreases from the impeller rim toward the central axis. Frequency-domain results indicate that most cases are dominated by the blade-passing frequency, whereas the counter-rotating guide vanes show a response nearly twice this frequency.

Rupture propagation and tunnel response in sandy overburden under dip-slip fault dislocation: Insights from physical test and numerical simulation - Huiling Zhao; Liming Liu; Haitao Yu (Tunnelling and Underground Space Technology, 2026)

Nanocellulose-based ion-exchange membranes for salinity-gradient osmotic energy conversion - Xinlei Yu; Liming Zhang; Honglin Che; Mengyu Liu; Jinghuan Chen; Chao Tian; Jingwei Chen; Minghua Huang; Jingyi Wu; Huanlei Wang; Feng Xu; Weiqian Tian (Carbohydrate Polymers, 2026)

Forward-Looking Sonar Based 6D Pose Estimation Using Acoustic-Yolo6D Detection and AnP Inversion: A Case Study for Subsea Christmas Tree Panel - Jinxing Yu; Sanming Song; Liming Li; Yuyang Lu; Taofeng Wang; Hairui Cao; Jiaxin Dong; Weilin Zang; Adam Rushworth; Bailu Si; Miaomou Chen (Journal of Marine Science and Engineering, 2026)
Subsea Christmas trees are often deployed in turbid coastal waters or seabed environments. During manipulator operations on Christmas tree panels, conventional optical servoing is severely limited by rapid electromagnetic attenuation and strong scattering from suspended particles, resulting in reduced visibility. Forward-looking sonar (FLS) provides stable imaging, but its unique imaging geometry and low resolution make direct 6D pose estimation challenging. To address this issue, this paper proposes a 6D object pose estimation method for FLS images, in which conventional optical control-point-based pose estimation is restructured to resolve the mismatch between optical-centric network assumptions and acoustic imaging characteristics, and is further integrated with acoustic projection-based pose inversion. First, to address the limited diversity of target appearances and the scarcity of training data, we construct an FLS imaging model based on primary truncation for image simulation, providing data for model pretraining. Second, a multi-task acoustic control-point detection network, Acoustic-Yolo6D, is designed to mitigate localization degradation caused by heavy speckle noise, low boundary contrast, and resolution variations associated with polar-coordinate imaging, through heatmap regression, auxiliary object segmentation, and explicit range-bearing positional encoding. An Acoustic-n-Point (AnP) model is then used to recover the target 6D pose. Finally, simulation and water-tank experiments on the socket target verify the feasibility and robustness of the proposed method under limited-data conditions. The method achieves a 3.1 cm mean translation error, a 10.88° mean orientation error, and 52 FPS in real underwater acoustic environments.

Dietary bamboo vinegar powder supplementation mitigates the adverse effects of a high-starch diet on growth performance, liver health, and glucose-lipid metabolism in largemouth bass (Micropterus salmoides) - Weibin Lai; Zhangyi Xiao; Ran Yu; Linyi Li; Wenqian Chen; Yuan Gao; Manqi Yang; Liangliang Zhang; Liming Lu; Jianchun Jiang (Frontiers in Marine Science, 2026)
This study explored the potential of bamboo vinegar powder (BVP) to mitigate hepatic injury and metabolic disturbance induced by a high-starch diet in largemouth bass ( Micropterus salmoides ). Fish were distributed into three groups (with three replicates per group) and fed for 56 days with a basal diet (BD), a high-starch diet (CSD), and the BVP-supplemented diet (CSDB, added 2.0 g/kg BVP to the CSD diet), respectively. After the feeding trial, fish in the CSD group exhibited a significant decrease in weight gain rate (WGR) and an increased hepatosomatic index (HSI) ( P < 0.05). Concurrently, hepatic glucose and lipid metabolism of fish in the CSD group were suppressed, leading to the accumulation of hepatic lipids and glycogen, along with histopathological manifestations such as hepatic vacuolation and nuclear shift. Furthermore, immune competence and hepatic antioxidant status were also compromised. However, relative to the CSD group, fish in the CSDB group demonstrated significant improvements in growth performance, immune function, and liver injury. Furthermore, BVP upregulated the expression of nuclear factor erythroid 2-related factor 2 ( nrf2 , a key regulator of antioxidant defense) and downregulated the nuclear factor kappa B ( nf - κb , a central transcription factor in inflammation) ( P < 0.05). More importantly, BVP might improve the metabolism of hepatic glucose and lipid in fish, by suppressing gluconeogenesis and promoting glycolysis to optimize glucose metabolism, as well as by inhibiting lipogenesis and promoting both lipid transport and catabolism to enhance lipid metabolism. Notably, dietary BVP supplementation significantly altered hepatic metabolite profiles, affecting pathways such as alpha-linolenic acid and arachidonic acid metabolism, and increasing the levels of several lipid metabolites, including docosahexaenoic acid and phosphatidylethanolamine species, compared to the CSD group ( P < 0.05). Collectively, these results demonstrated that BVP improved growth performance, liver health, and glucose-lipid metabolism in largemouth bass fed a high-starch diet.

Archean microplates: Reconstruction methods and their resource-environmental effects - Guozheng Sun; Jianping Zhou; Sanzhong Li; Shuwen Liu; Xi Wang; Jian Kuang; Liangliang Wang; Lintao Wang; Yang Yu; Lei Gao; Yalu Hu; Shengyao Yu; et al. (Earth-Science Reviews, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

An intelligent synthetic biomarker-based theranostic nanoplatform for ultrasensitive microtumor detection via noninvasive urinary analysis - Liming Miao; Wang Yu; Xiaodan Jia; Yue Wang; Xiue Jiang (Science Bulletin, 2026)

Unlocking microbial synergy in microalgae-bacteria granules: RSM-driven optimization and lifecycle microbial metagenomics for high-ammonia wastewater treatment - Yanni Geng; Chun-Ang Lian; Liming Yang; Spyros G. Pavlostathis; Xuejiao Qiao; Zhiguang Qiu; Yu Wang; Nan Dong; Anjie Li; Xubiao Luo; Ke Yu (Water Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Development of biodegradable multifunctional zein-curcumin-quercetin-chondroitin sulfate nanoparticles with cold plasma-modified chitosan-based active film for tilapia preservation - Tingting Yang; Xinming Zhang; Feifei Wang; Liming Zhang; Dawei Yu; Xueying Zhang; Guanghua Xia; Jiamei Wang (Food Hydrocolloids, 2026)

Non-uniform and Non-linear background correction methods for ionospheric TEC changes detection associated with solar eclipse - Liming He; Yu Zhang; Ronghua He; Zhixiang Liu; Zhengqi Zhao; Xiukang An (GPS Solutions, 2026)

Trade‐Off Between Hydraulic Performance and Filtration Level of Screen Filters Under Different Inlet Pressures and Screen Apertures - Kai Zhang; Jaume Puig‐Bargués; Peng Hou; Yang Xiao; Liming Yu; Yunkai Li (Irrigation and Drainage, 2026)
Screen filters (SFs) are widely used for water purification. Particles adhered to the SF surface can block flow channels and potentially result in changes in the SF filtration level. However, the impact of blockage on the actual filtration level and hydraulic performance of SF remains uncertain. This study investigated the effects of five inlet pressures (0.02, 0.04, 0.06, 0.08 and 0.10 MPa) and seven screen apertures (125, 150, 180, 210, 250, 300 and 355 μm) on the filtration effectiveness, head loss and flow rate of agricultural SF. The results revealed that blockage reduced the SF pore size by 16%–45%, increasing the filtration level. An increased inlet pressure accelerated SF blockage and increased the filtration level, reducing the pore size by 14%–35% at 0.10 MPa, compared with 0.02 MPa. However, an improved filtration level led to greater head loss. A trade‐off between screen aperture and head loss was identified, suggesting the need for practical SF filtration level adjustments. For the 210 μm filtration requirement, the use of a 250 μm filter at 0.06 MPa or a 300 μm filter at 0.08 MPa achieved the desired aperture while minimizing head loss. Compared with selecting filters solely on the basis of pore size, adjusting the filtration level increased the average flow rate by 23% and decreased the average head loss by 25%. This study provides significant insights into SF filtration grade changes and offers a strategy to reduce filtration energy consumption.

The solubilization effects and microscopic mechanisms of a novel sugar-based Gemini surfactant for multiple DNAPLs - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2026)

CO2-responsive gel microsphere system for carbon sequestration and enhanced oil recovery in harsh reservoirs: Experimental study and molecular dynamics simulation - Jianing Yu; Xu Li; Haifeng He; Zhimin Peng; Liming Zheng; Jianming Yu; Chenrui Yang; Jun Wei (Fuel, 2026)

Exploring the potential mechanism of Chinese herbal medicine Fuzi on aplastic anemia based on UHPLC-MS/MS method combined with network pharmacology and molecular docking - Wenjian Wei; Yuping Si; Zonghong Li; Xuewei Yin; Guodong Ma; Jingbo Shi; Changnian Li; Liming Yu; Wei Zheng; Yan Wang; Kui Liu; Ruirong Xu; et al. (Natural Product Research, 2025)

Information fusion of slurry concentration, particle size and LIBS data for iron grade analysis in mineral processing industry - Peng Zhang; Tong Yu; Lanxiang Sun; Haibin Yu; Lifeng Qi; Liming Zheng (Minerals Engineering, 2025)

CO2-responsive gels for enhanced oil recovery and carbon sequestration: A comprehensive review of design and applications - Jianing Yu; Xu Li; Ruobing Qiao; Liming Zheng; Nasir Khan; Haifeng He; Zhimin Peng; Yanhua Yu (Journal of Environmental Chemical Engineering, 2025)

Preparation of tuna skin gelatin–polyphenol intelligent packaging film and its application in the preservation of tuna - Hao Zeng; Qinghe Yin; Hui Sun; Liming Zhang; Tao Yang; Kai Wang; Haohao Shi; Jiamei Wang; Guanghua Xia; Yongqiang Zhao; Gang Yu (Food Chemistry, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Hydrophilic anions for expanding the electrochemical stability window of water-in-salt electrolytes - Jianglin Fu; Xuzhe Li; Yubing Li; Yu Li; Ziyue Yu; Liming Lei; Shuaikai Xu; Tangming Mo; Yu Long (Chemical Engineering Journal, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Structural evolutionary process and ore-controlling model of the Shuicheng Sn-Pb-Zn deposit, SW China - Liming Ouyang; Huan Li; Han Zheng; Mohamed Faisal; Junpeng Yu; Yongfang Jiang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

ARABIDOPSIS NITRATE REGULATED 1 negatively regulates the tolerance of salt stress by controlling ion homeostasis and GA metabolism - Heekyung Lee; Eun Kyu Ko; Juyeon Park; Yu-Jin Jang; Kang-Mo Ku; Liming Xiong; Hojoung Lee (Journal of Plant Physiology, 2025)

Numerical investigation of the effect of H2 and O2 addition on laminar counterflow flames of ammonia: A comparative study - Liming Dai; Wenzhao Ma; Qian Wang; Ulrich Maas; Chunkan Yu (Fuel, 2025)

Enzymatic hydrolysis of cassava leaf proteins unlocks antioxidant and therapeutic peptides: Alcalase-derived bioactives target oxidative stress pathways - Jinquan Zhang; Yusi Fang; Zuoda Zhang; Houmei Yu; Liming Lin; Qinfei Wang; Zhenwen Zhang; Yong Song (Food Chemistry, 2025)

Combined non-volatile and volatile metabolite profiles and antioxidant activities reveal the enhancement of traditional “steaming and Sun-drying nine times” on the functional properties of jujube - Yu Liu; Lijuan Zhang; Haijiao Lin; Zengyi Song; Pu Xu; Liming Zhang; Binbin Wei (Food Chemistry, 2025)

Synergistic diatomic sites 2Ag-MOFs promoting high-efficiency electrocatalysis of CO2 at ultralow overpotential: Bridged O-bound intermediate - Liming Hong; Yue Hong; Luliang Liao; Minxing Shua; Qiming Yu; Hongming Wang (Chemical Engineering Journal, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Investigation of transport and deposition behavior and mechanisms of micro-nano-bubbles in porous media - Yazhou Cao; Dantong Lin; Zhen-Yu Yin; Liming Hu (Journal of Hydrology, 2025)

Unveiling DNAPLs solubilization mechanisms: How hydrophobic chain length governs characteristics in novel sugar-based Gemini surfactants - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Chengwu Zhang; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2025)

Label-free quantitative proteomics to exploit the impact of active films on texture stabilization of refrigerated carp fillets - Liming Zhang; Dawei Yu; Yanshun Xu; Qixing Jiang; Dongxing Yu; Wenshui Xia (Food Chemistry, 2025)

N–doped carbon coating boosts the construction of high–performance regenerated LFP cathodes - Yifeng Li; Haoxuan Yu; Yuan Ding; Meiting Huang; Yaohui Xie; Peilin Li; Zhihao Wang; Lihua Wang; Liang Chen; Xubiao Luo; Liming Yang (Chemical Engineering Journal, 2025)

Moisture-adaptive cellulose/MXene aerogels for synergistic moisture and triboelectric energy harvesting - Jiwei Zhang; Xinran Zhou; Mengjie Wu; Liming Zhu; Zechang Ming; Weikang Li; Yong Xia; Hao Liu; Zijie Zhou; Tao Zhang; Minghui Fan; Jianyong Yu; et al. (Chemical Engineering Journal, 2025)

MAO-A inhibition alleviates sepsis-driven lung injury via Nrf2/HO-1 pathway activation and suppression of pyroptosis - Min Li; Hu Li; Liming Gong; Xinmin Chen; Jincan Dai; Jirong Tian; Xiaochuan Yin; Qinghe Yu (Journal of Molecular Histology, 2025)

Study on the Vortex Characteristics and Wear of Centrifugal Pump Based on Field‐Force Coupling Method - Tiantian Wang; Diyi Chen; Liming Yu; Qiangqiang Sun; Lintong Zhang (Irrigation and Drainage, 2025)
To examine the vortex and wear characteristics of high‐speed centrifugal pumps, a field force coupling method was employed via the Application Programming Interface (API) of Engineering Discrete Element Model (EDEM) software and Field Data Manager functions. This approach seeks to analyse variations in vortex patterns across distinct flow fields and the wear characteristics of centrifugal pump components subjected to different particle sizes. The results reveal that with increasing flow rates, the weak vortex within the centrifugal pump diminishes, whereas the strong vortex intensifies. The vorticity in the volute decreases by 12%, whereas the vorticity at the front and rear pump covers, as well as the impeller blades, increases by 11% and 25%, respectively. Using the Q criterion, λ 2 criterion, and regularized helicity, vortex changes within the centrifugal pump were precisely captured. The vortex structure within the centrifugal pump predominantly consists of a separation vortex in the impeller blade region and a vortex at the inlet and outlet pipelines. Vortex formation initiates at the leading edge of the blade and propagates toward the pipes and other components. An analysis of the normal and radial energies demonstrated that the sliding friction of the particles was the principal wear mechanism in the centrifugal pump. The volute endures the most substantial wear, primarily at its front section. As the flow rate increases, the amount of wear on the volute progressively diminishes. With increasing particle radius, regions of severe wear within the centrifugal pump extend progressively from Volute Section VIII to Section VII, and blade wear becomes more pronounced.

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

A novel method to repair and upgrade spent LFP cathode material by inherent Al impurity doping - Haoxuan Yu; Derun Zhao; Kechun Chen; Meiting Huang; Haitao Yang; Liming Yang; Zhihao Wang; Liang Chen; Xuan Ding; Hui Lv; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Data-driven insights to tackle photo-induced phase segregation for mixed-halide perovskite solar cells - Yuhui Jiang; Yu Zheng; Jingfan Li; Yang Pu; Liming Du; Yangyang Guo; Ning Jia; Xu Zhang; Yerzhan Mukhametkarimov; Ruihao Chen; Zhe Liu; Hongqiang Wang (Chemical Engineering Journal, 2025)

Delivery of penetration-enhancing antioxidant polyphenol nanoparticles with Codonopsis pilosula polysaccharide microneedles for synergistic treatment of psoriasis - Siqi Liu; Silu Song; Yu Zhang; Liming Yan; Yuhui Chen; Wanrong Li; Banaz Jalil; Chun Wu; Yuping Fu; Xingfu Chen; Jingyi Gu; Lixia Li; et al. (Carbohydrate Polymers, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Real-time detection of plasmin activity in milk using an ordered porous layer interferometry - Liming Liu; Lu Wang; Ning Ma; Yu Zhang; Yi-Zhen Wan; Tianze Wang; Bo Zhang; Qianqian Su; Shaohua Ding; Weiping Qian (Food Chemistry, 2025)

Multifunctional treatment of food waste liquefied liquid by algal-bacterial microbial fuel cells: water, electricity and biomass nexus and mechanism profiling - Liming Hu; Yu Hong; Jiale Liu; Zeyuan Wang; Xiaoyan Wang; Yujia Gao (Algal Research, 2025)

Micron-scale heterogeneity reduction leads to increased interspecies competition in thermophilic digestion microbiome - Liming Chen; Bixi Zhao; Miao Zhang; Yuxi Yan; Cailong Nie; Kaiqiang Yu; Zhihao Tu; Yu Xia (Water Research, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Rapid production of zein/polyethylene oxide film containing dihydroquercetin by green solution blow spinning for yellowfin tuna preservation - Hui Sun; Liming Zhang; Qinghe Yin; Tao Yang; Kai Wang; Haohao Shi; Jiamei Wang; Guanghua Xia; Yongqiang Zhao; Gang Yu (Food Packaging and Shelf Life, 2025)

A hydraulic conductivity model incorporating adsorption and capillarity for unsaturated/frozen soil - Yijie Wang; Yandi Wu; Liming Hu; Pierre-Yves Hicher; Zhen-Yu Yin (Engineering Geology, 2025)

Inherent fluorine impurity enhances the regeneration of highly degraded layered cathodes with suppressed lattice oxygen escape - Meiting Huang; Haoxuan Yu; Liang Chen; Haitao Yang; Zhihao Wang; Yifeng Li; Kechun Chen; Chenxi Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Urbanization enhances soil nitrogen mineralization mainly by increasing particulate organic nitrogen fractions in urban park greenspaces: A case study in Hangzhou, China - Bo Fan; Yuye Shen; Yan Wang; Liming Yin; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Applied Soil Ecology, 2025)

DeepSeek-Based Multi-dimensional Augmentation of Short and Highly Domain-Specific Textual Inquires for Aquaculture Question-Answering Framework - Liming Shao; Hong Yu; Wei Huang; Huiyuan Zhao; Lixin Zhang; Jing Song (Aquaculture International, 2025)

Impacts of landscape factors on gully retreat and its morphological characteristics in hilly areas of Northeast China - Peng Jiao; Yang Ou; Shujiang Pang; Baixing Yan; Yu Zhang; Wenxu Xu; Liming Yan (Soil and Tillage Research, 2025)

The molecular mechanism of ovary development in Thamnaconus septentrionalis induced by rising temperature via transcriptomics and metabolomics analysis - Yan Liu; Wengang Xu; Xueli Zhang; Jiulong Wang; Xiaoling Chen; Xiaoyan Yu; Jun Zeng; Yanqing Wu; Liming Liu (Frontiers in Marine Science, 2025)
The greenfin horse-faced filefish, Thamnaconus septentrionalis , which is widely distributed in the Indo-West Pacific Ocean, is an important commercial fish species with characteristic blue-green fins, rough skin, and a spine-like first dorsal fin. Recently, T. septentrionalis has captured the attention of conservation and development due to its sharply declining population, and its great economic value as an important marine aquaculture fish species. To protect the resources of T. septentrionalis and develop its fishery industry, artificial breeding is essential and has been carried out gradually in local farms in China. A previous study has shown that temperature can effectively influence the gonadal development in T. septentrionalis in its overwintering state. However, the molecular mechanisms underlying the effects of temperature on the gonadal development in T. septentrionalis are still unrevealed and worth further study. In the present study, we systematically investigated the effects of temperature on ovary development in T. septentrionalis through transcriptomics and metabolomics analysis. The results showed that temperature rises significantly regulated the metabolic status of T. septentrionalis and promoted ovary development and maturation process through the regulation of the pathways of ECM-receptor interaction, regulation of actin cytoskeleton, oocyte meiosis, steroid hormone biosynthesis, lipid metabolism, ABC transporters, protein digestion and absorption, biosynthesis of amino acids pathways, etc. The histological, scanning electron microscope, and transmission electron microscope analyses showed that the oocytes in the ovaries of T. septentrionalis experiencing the temperature rises developed from phase II to III with increased gonadal somatic index and 17β-estradiol level. The present study for the first time elucidated the potential molecular regulatory mechanism of ovary development in T. septentrionalis induced by temperature and will provide valuable information for the artificial breeding of T. septentrionalis and conservation of T. septentrionalis fishery resources in the future.

Structural design and performance optimization of an anionic-nonionic Gemini surfactant for remediation of perchloroethylene-contaminated aquifers - Liming Ren; Lijuan Yu; Honghuan Xia; Rui Zhao; Yu Yao; Yongsheng Zhao; Chuxuan Zhao; Bing Qin; Chuanyu Qin (Journal of Environmental Chemical Engineering, 2025)

Regulation of the colloidal organic matter in coastal waters by scallop farming - Bin Wang; Xuelu Gao; Liming Wang; Xiaoxiao Yu; Yongliang Liu; Xiyan Sun; Jianmin Zhao; Qianguo Xing; Yuwei Yang (Marine Environmental Research, 2025)

Association of residential greenness and sleep duration in adults: A prospective cohort study in China - Jiayi Li; Yaoyao Lin; Zongming Yang; Joachim Heinrich; Tianyu Zhao; Zhebin Yu; Wenqing Wang; Kaixuan Yang; Peng Shen; Hongbo Lin; Liming Shui; Jianbing Wang; et al. (Environmental Research, 2025)

Dietary bamboo vinegar powder improves growth performance, immunity, antioxidant capacity and lipid metabolism of largemouth bass (Micropterus salmoides) - Weibin Lai; Shuwen Xu; Ran Yu; Linyi Li; Yuanyi Zuo; Manqi Yang; Liangliang Zhang; Liming Lu; Yong Xu; Yiwen Liu; Hua Wang; Jianchun Jiang (Animal Feed Science and Technology, 2025)

Neoarchean orogenic belt evolution in the northeast North China Craton: Implications for the reconstruction of early Earth’s microplates - Guozheng Sun; Shuwen Liu; Sanzhong Li; Timothy M. Kusky; Fangyang Hu; Han Bao; Lei Gao; Yalu Hu; Shengyao Yu; Liming Dai; Lintao Wang; Xi Wang (Precambrian Research, 2025)

Machine learning-based strength prediction for circular concrete-filled double-skin steel tubular columns under axial compression - Shou-Zhen Li; Jin-Jin Wang; Liming Jiang; Ran Deng; Yu-Hang Wang (Engineering Structures, 2025)

Spatiotemporal metabolic mapping of ex-situ preserved hearts subjected to dialysis by integration of bio-SPME sampling with non-targeted metabolipidomic profiling - Mariola Olkowicz; Frank Yu; Juglans Souto Alvarez; Roberto Vanin Pinto Ribeiro; Roizar Rosales; Liming Xin; Miao Yu; Karol Jaroch; Mitchell Brady Adamson; Ved Bissoondath; Filio Billia; Mitesh Vallabh Badiwala; et al. (Analytica Chimica Acta, 2025)

Distribution characteristics and ecological risk assessment of heavy metal pollution in seawater near the Yellow River Estuary of Laizhou Bay - Xiaojie Jin; Jichen Liu; Liming Wang; Xiaoxiao Yu; Jiaying Wang; Yang Jin; Shaonan Qiu; Jiaqi Liu; Yuting Zhao; Shan Sun (Marine Environmental Research, 2025)

In-depth understanding of high temperature and low residence time on the corn straw rapid pyrolysis char structure evolution - Xinyu Wang; Teng Ma; Hanxiao Liu; Yang Liu; Bo Yu; Yumin Chen; Liming Wu; Ming Zhai; Huaichun Zhou (Fuel, 2025)

Self-adaptation of tolerant microalgae-bacterial consortia in landfill leachate: Simultaneous achievement of efficient nitrogen removal and value-added utilization - Yanni Geng; Chun-Ang Lian; Liming Yang; Spyros G. Pavlostathis; Zhiguang Qiu; Xuejiao Qiao; Zhensheng Xiong; Nan Dong; Jincheng Hu; Xubiao Luo; Ke Yu (Chemical Engineering Journal, 2025)

PbI2 intercalation and residual elimination strategy for sequential inverted perovskite solar cells - Zhuowei Du; Zhu Ma; Tangjie Yu; Zhangfeng Huang; Shanyue Hou; Qianyu Liu; Yanlin Li; Yi Chen; Qiang Yang; Wei You; Junbo Yang; Hao Du; et al. (Chemical Engineering Journal, 2025)

The importance of porewater exchange process on carbon lateral export from saltmarsh creek to coastal sea - Jian’an Liu; Xueqing Yu; Xinyi Lin; Tong Peng; Liming Xue; Jinzhou Du (Journal of Oceanology and Limnology, 2025)

Hysteresis at low humidity on vapor sorption isotherm of Ca-montmorillonite: The key role of interlayer cations - Yijie Wang; Zhen-Yu Yin; Pierre-Yves Hicher; Liming Hu (Applied Clay Science, 2025)

Molecular characterization of a novel victorivirus isolated from Stagonosporopsis citrulli - Xiaofang Ma; Xing Zhang; Lifeng Zhai; Yingchun Jiang; Peter Moffett; Yu Zhang; Fang Song; Xin Song; Zhijing Wang; Ligang He; Shengmei Ji; Liming Wu (Archives of Virology, 2025)

Treatment of sludge hydrothermal carbonization wastewater by ferrous/sodium percarbonate system: Effect of wastewater composition and role of coagulation and oxidation - Liming Liu; Luna Zhao; Shiyun Jin; Wei Zou; Hongxia Wang; Yu Xie; Changlan Hou; Yunbo Zhai; Pingping Luo (Water Research, 2024)

Susceptibility assessment of glacier-related debris flow on the southeastern Tibetan Plateau using different hybrid machine learning models - Rui Yu; Rui Guo; Liming Jiang; Yi Shao; Zhiwei Zhou (Science of The Total Environment, 2024)

Comparation of pheromone-binding proteins 1 and 2 of Spodoptera frugiperda in perceiving the three sex pheromone components Z9-14:Ac, Z7-12: Ac and Z11-16: Ac - Liming Hu; Taoli Zhang; Qingjun Wu; Kangyuan Liang; Guohui Yu; Muyang He; Dasong Chen; Xiangning Su; Yuping Zhang; Zhenfei Zhang; Jianmei Shen (Pesticide Biochemistry and Physiology, 2024)

Organic carbon burial dynamics at the Chukchi Shelf margin: Implications for the Arctic Ocean carbon sink - Liming Ye; Xiaoguo Yu; Yanguang Liu; Anatolii S. Astakhov; Alexander Bosin; Yeping Bian; Linsen Dong; Weijia Fan; Haili Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Paralichthys olivaceus GSDME-mediated pyroptosis is regulated by multiple caspases in different manners - Kangwei Hao; Liming Yuan; Chao Yu; Hang Xu; Li Sun (Fish & Shellfish Immunology, 2024)

Multiple hydrogen bonding induced by semi-interpenetrating polymer network binder to enhance the electrochemical performance of sodium-ion batteries electrodes - Liming Yu; An Chen; Ruixian Tang; Fangfang Zhao; Jinjin Li; Liangming Wei (Chemical Engineering Journal, 2024)

Enhancing nitrogen removal in combined sewage overflows by using bio-fluidized bed with ceramic waste powder carriers: effects and mechanisms - Zian Zhou; Xinyuan Zheng; Yinghao Hua; Meixin Guo; Xiaoting Sun; Yan Huang; Liming Dong; Suping Yu (Environmental Science and Pollution Research, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Centrifugation-modulated uniform antibacterial paper with well-interconnected hierarchical pores for flexible high-sensitivity humidity monitoring - Tongtong Qin; Zhengpeng Yang; Huili Fu; Liming Zhao; Zhenzhong Yong; Li Chen; Kunjie Wu; Chenxuan Li; Chunjing Zhang; Yongyi Zhang; Yufang Cao; Hengyi Yu; et al. (Chemical Engineering Journal, 2024)

Lead iodide secondary growth and π-π stack regulation for sequential perovskite solar cells with 23.62% efficiency - Zhangfeng Huang; Zhuowei Du; Zhu Ma; Yujie Zheng; Qian Zhang; Wei You; Junbo Yang; Tangjie Yu; Shanyue Hou; Guoming Li; Hao Du; Yixian Li; et al. (Chemical Engineering Journal, 2024)

Comprehensive analysis of hyperspectral features for monitoring canopy maize leaf spot disease - Yali Bai; Chenwei Nie; Xun Yu; Mingyue Gou; Shuaibing Liu; Yanqin Zhu; Tiantian Jiang; Xiao Jia; Yadong Liu; Fei Nan; Liming Li; Bedir Tekinerdogan; et al. (Computers and Electronics in Agriculture, 2024)

Statistical study of BDS-2/BDS-3 satellite signal quality and positioning accuracy during weak and moderate geomagnetic storms - Liming He; Zhixiang Liu; Ronghua He; Zhenglin Qu; Yu Zhang; Zenghui Qin (Advances in Space Research, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Deciphering the adaptation mechanism of anammox consortia under sulfamethoxazole stress: A model coupling resistance accumulation and interspecies-cooperation - Cailong Nie; Liming Chen; Bixi Zhao; Ziqi Wu; Miao Zhang; Yuxi Yan; Bing Li; Yu Xia (Journal of Hazardous Materials, 2024)

Strong light-trapping probes with high antibody activity for sensitive detecting FB1 by “turn-on” lateral flow immunoassay - Sha Yu; Gan Zhang; Liming Hu; Huayuan Ji; Jiawei Chen; Juan Peng; Weihua Lai (Chemical Engineering Journal, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Improved photocatalytic property of ZnO by simultaneously integrating with Ag3VO4 for constructing a heterojunction and biochar as charge transfer bridge via microwave hydrothermal method - Weimeng Chi; Fei Yu; Guohua Dong; Liming Bai; Dongxuan Guo; Dong-Feng Chai; Ming Zhao; Jinlong Li; Wenzhi Zhang (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “The effect of postharvest water migration on metabolism of cassava root by hypobaric storage” [Innovative Food Science and Emerging Technologies, 93 (May 2024)103609] - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Effects of Micropores on the Vapor Sorption Isotherm and Structural Parameters Characterization of Kaolinite - Yijie Wang; Liming Hu; Zhen-yu Yin (Computers and Geotechnics, 2024)

Natural deep eutectic solvents pretreatments for sludge dewaterability improvement and subsequent volatile fatty acids production: Insights of sludge disintegration and metagenomic characterization - Xiaoping Liu; Yunbo Zhai; Zhixiang Xu; Fashen Liang; Wanying Ren; Yu Xie; Jintong Ma; Liming Qin; Hongkui He (Chemical Engineering Journal, 2024)

Meta-analysis of root-associated bacterial communities of widely distributed native and invasive Poaceae plants in Antarctica - Xumin Wang; Ying Qu; Xindong Teng; Li Xu; Liming Jin; Hao Xue; Zhuoran Xun; Qingzheng Zhang; Chenghong Wang; Lijun Wang; Xiumei Liu; Shuang Wang; et al. (Polar Biology, 2024)

CO2 mineralization and utilization by tailings sand in China for potential carbon sinks and spatial project layout - Huaqing Li; Yahui Bian; Mingliang Liu; Jianyi Lin; Min Dai; Hongyi Xie; Huajun Yu; Bin Chen; Meili Xue; Zhiwei Li; Jingjing Yin; Liming Xue (Resources, Conservation and Recycling, 2024)

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

Effect of inlet velocity on the hydraulic and filtering performance of a Y‐type screen filter - Na Li; Junfeng Li; Liming Yu; Wenhan Yang; Xuelian Liu; Qiao Cheng (Irrigation and Drainage, 2024)
Uneven sediment distribution affected by inlet velocity, particle size distribution and flow field characteristics leads to local clogging in a Y‐type screen filter. This study revealed the detailed flow field characteristics and distribution of sediments on the screen via computational fluid dynamics combined with the discrete element method (CFD–DEM) simulations and experimental tests. The results showed that the distribution of the flow rate on the filter screen was extremely uneven, with the maximum flow rate being 11.72 times greater than the minimum rate. The flow rate was distributed symmetrically on the two sides along the outlet centreline, as shown by the unfolded drawing of the filter core. Numerical simulation and experimental tests using sandy water showed that the number and average particle diameter on the screen decreased, and the number and average particle diameter in the plug increased, with increasing inlet velocity. The sediments on the screen were distributed intensively, and the plugging extent coefficient and the anti‐clogging performance improved. However, this process was more likely to cause local clogging and worsen the filtration performance. Therefore, low‐speed filtering should be applied if the filtering effect is needed, and high‐speed filtering should be applied if the filtering efficiency is favourable but the flushing frequency increases.

Effectiveness of biological drying for citric acid dewatered sludge: Evaluating the impact of energy-efficient ventilation strategies - Chen Zhang; YangYang Li; ZhanQiu Yu; YanFeng Liu; LiMing Dong (Waste Management, 2024)

Development and performance evaluation of wind field automatic control system for raisin drying room - Shuai Ma; Liming Xu; Shucai Xu; Mingqun Yu; Haochao Tan; Chenggong Yan; Congcong Shen (Journal of Food Engineering, 2024)

Fe-doped CeTiOx catalysts facilitate the oriented oxidation of NO to achieving simultaneous desulfurization and denitration in a WFGD system - Lei Zhou; Zhixiang Wei; Junkang Fan; Qingqing Yu; Chuang Zhao; Jie Zhang; Liming Yang; Weili Dai; Linjun Yang (Fuel, 2024)

Neoarchaean DTTGs from the Dunhuang Block, Tarim Craton: insights into petrogenesis and crust–mantle interactions - Lintao Wang; Shengyao Yu; Guozheng Sun; Pei Lv; Yinbiao Peng; Xingzhou Jiang; Liming Dai; Yongjiang Liu; Sanzhong Li (International Geology Review, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

The effect of postharvest water migration on metabolism of cassava root by hypobaric storage - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Green halochromic smart and active packaging materials based on chitosan film loading nanoparticles: Functionality, physicochemical properties and application - Liming Zhang; Dawei Yu; Yulu Gu; Yanshun Xu; Qixing Jiang; Fang Yang; Joe M. Regenstein; Dongxing Yu; Wenshui Xia (Food Hydrocolloids, 2024)

Identification of the C1qDC gene family in grass carp (Ctenopharyngodon idellus) and the response of C1qA, C1qB, and C1qC to GCRV infection in vivo and in vitro - Le Yang; Chong Wang; Yuhong Huang; Baohong Xu; Yi Liu; Jianbo Yu; Liming Xiong; Tiaoyi Xiao; Qiaolin Liu (Fish & Shellfish Immunology, 2024)

Ion migration mechanism of electrochemical water softening in dual-chamber reactors and their performance for real circulating cooling water - Wenda Kang; Jiyuan Xu; Yingxin Xie; Liming Yan; Kun Zhao; Xinying Gong; Hongtao Yu (Journal of Cleaner Production, 2024)

Deep eutectic solvents pretreatment enhances methane production from anaerobic digestion of waste activated sludge: Effectiveness evaluation and mechanism elucidation - Yu Xie; Xiaoping Liu; Liming Liu; Yin Zhou; Zhexian Wang; Cheng Huang; Hongkui He; Yunbo Zhai (Journal of Environmental Management, 2024)

Effect of chitosan and chitosan oligosaccharide on the interaction and in vitro gastric digestive behavior of whey protein isolate - Ning Ma; Liming Liu; Yu Zhang; Lu Wang; Weiping Qian (Food Hydrocolloids, 2024)

Enhancing bioavailable carbon sources and minimizing ammonia emissions in distillery sludge and distiller's grains waste co-composting through deep eutectic solvent addition - Fashen Liang; Xiaoping Liu; Xin Yu; Liming Liu; Hongkui He; Cheng Huang; Jie Hu; Zhexian Wang; Yin Zhou; Yunbo Zhai (Bioresource Technology, 2024)

A regional attentive empirical orthogonal function analysis: An application to North Atlantic Oscillation - Dongshuang Li; Liming Pan; Jian Wang; Chunhua Shi; Zhaoyuan Yu; Linwang Yuan (International Journal of Climatology, 2024)
Empirical orthogonal function (EOF) analysis is widely adopted for identifying spatial patterns in regular latitude‐longitude gridded geographical data. However, a standard EOF analysis could underestimate variances from low latitudes due to the increasing grid cell areas when moving toward the equator. A broadly adopted compensating approach is the area‐weighted EOF, where the grid data are multiplied by a factor proportional to the grid area, thereby forcing each datum to represent identical areas. In this article, we revisit the area‐weighting scheme and discuss its potential drawbacks. In particular, we show that along with compensating the unequal areas, another unaddressed issue is which region of the data is more relevant to our focused problem. We propose a regional attentive EOF (RA‐EOF) method, which resolves area‐compensation and region selection simultaneously. We conduct case studies of the North Atlantic Oscillation (NAO) analysis and perform RA‐EOF to the sea level pressure variability in the North Atlantic sector. Experiments show that our method evidently detects the NAO pattern in the leading mode of sea level pressure variability and suggests the southwestward movement of the southern action centre of NAO during the summers. Our findings clarify the ambiguity about the summer NAO in previous studies. The proposed methodology provides a potent instrument for discerning the spatial distribution and analysing the temporal variability of atmospheric teleconnections and oscillations, particularly in cases characterized by weak signal strength.

Metagenomic insights into protein degradation mechanisms in natural fermentation of cassava leaves - Jinquan Zhang; Qinfei Wang; Houmei Yu; Liming Lin; Zhenwen Zhang; Yong Song (Bioresource Technology, 2024)

Influence of Lithology on the Stability of Organic Carbon in Typical Soils of Karst in Northwest China - Lening Hu; Liming Zhou; Rui Qin; Hua Deng; Jianing Zhang; Yuefeng Yu; Tieguang He (Journal of Soil Science and Plant Nutrition, 2024)

Predicting the Fishery Ground of Jumbo Flying Squid (Dosidicus gigas) off Peru by Extracting Features of the Ocean Environment - Tianjiao Zhang; Jia Xin; Wei Yu; Hongchun Yuan; Liming Song; Zhuo Yang (Fishes, 2024)
We introduce a novel method that combines satellite data, advanced clustering techniques, machine learning feature extraction, and statistical models to enhance fishery forecasting accuracy. Focusing on jumbo flying squid in the southeast Pacific Ocean near Peru, we utilize MODIS-Aqua and MODIS-Terra satellite data on sea surface temperature (SST) to construct a deep convolutional embedded clustering (DCEC) model and extract the monthly SST features (FM) based on an optimized number of clusters determined by the Davies–Bouldi index (DBI). We use the extracted FM to construct a series of Generalized Additive Models (GAM) to forecast the catch per unit effort (CPUE) of jumbo flying squid within a spatial resolution of 0.5° × 0.5°. Our results demonstrate the following findings: (1) The SST feature clusters obtained through the DCEC model could capture the SST monthly variations; (2) The GAM models with FM outperform the models with the traditional monthly average SST in terms of predictive accuracy; (3) Using both FM and average SST together can further improve model performance. This study demonstrates the effectiveness of the DCEC combined with DBI in extracting marine environmental features and highlights the ocean environment feature extraction method to enhance the precision and reliability of fishery forecasting models.

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Recycling of spent lithium–ion battery graphite anodes via a targeted repair scheme - Kechun Chen; Yuan Ding; Liming Yang; Zhihao Wang; Haoxuan Yu; Difan Fang; Yufa Feng; Liying Hu; Chenxi Xu; Penghui Shao; Xubiao Luo; Liang Chen (Resources, Conservation and Recycling, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

Ionothermal synthesis of Cs3Bi2Br9 quantum dots-decorated covalent triazine frameworks composite photocatalyst and their application in selective cleavage of C–C bonds in lignin - Linglong Shi; Huifang Ma; Liming Dong; Shuangzhen Guo; Yu Liu; Da Li; Jianjie Wang; Shunli Li (Journal of Environmental Chemical Engineering, 2024)

Chitosan/alginate dialdehyde trilayer films with cinnamaldehyde nanoemulsions for grass carp preservation - Junli Dong; Dawei Yu; Liming Zhang; Guohao Wang; Pingping Zhang; Yitian You; Yanshun Xu; Wenshui Xia (Food Hydrocolloids, 2024)

Establishment and characterization of a novel hypopharyngeal squamous cell carcinoma cell line CZH1 with genetic abnormalities - Jingyu Ma; Xiaoke Zhu; Yu Heng; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Micromechanical Analysis of Lateral Pipe–Soil Interaction Instability on Sloping Sandy Seabeds - Yu Peng; Liming Qu (Journal of Marine Science and Engineering, 2024)
The micromechanical mechanism of pipe instability under lateral force actions on sloping sandy seabeds is unclear. This study investigated the effects of slope angle and instability direction (upslope or downslope) on pipe–soil interaction instability for freely laid and anti-rolling pipes using coupled discrete element method and finite element method (DEM–FEM) simulations. The numerical results were analyzed at both macro- and microscales and compared with the experimental results. The findings revealed that the ultimate drag force on anti-rolling pipes increased with slope angle and was significantly larger than that on freely laid pipes for both downslope and upslope instabilities. Additionally, the rotation-induced upward traction force was proved to be the essential reason for the smaller soil deformation around freely laid pipes. Moreover, the shape differences in the motion trajectories of pipes were successfully explained by variations in the soil supporting force distributions under different slope conditions. Additionally, synchronous movement between the pipe and adjacent particles was identified as the underlying mechanism for the reduced particle collision and shear wear on pipe surfaces under a high interface coefficient. Furthermore, an investigation of particle-scale behaviors revealed conclusive mechanistic patterns of pipe–soil interaction instability under different slope conditions. This study could be useful for the design of pipelines in marine pipeline engineering.

Study on the distribution and habitat suitability of seagrass in the Northern Chinese Seas - Zhenhua Wang; Qiaofeng Ma; Shuxiu Liang; Yu-an Liu; Liming Liu; Chao Huang; Kexin Chen; Wenhao Hou (Frontiers in Marine Science, 2024)
Seagrass plays an important role in global coastal ecosystems but is among the least conserved marine ecosystems. The Northern Chinese Seas have abundant seagrasses. However, the limited information on their distribution and habitat suitability has hindered seagrass conservation and restoration in this area. The maximum entropy (MaxEnt) model was developed to study the distribution and habitat suitability of seagrasses. First, the model was developed using seagrass occurrence points and environmental variables data. The predictions were visualized using ArcGIS to create a map of potential seagrass distribution. Next, the Jackknife analysis tool and contribution rate were used to identify and quantify the dominant environmental variables. The predictions were analyzed to quantify the suitable range of the dominant environmental variables and determine the conditions for seagrass habitat suitability in the study area. Finally, the predictions were re-analyzed. By coupling the previous predictions and re-analysis results, the areas and suggestions for seagrass conservation and restoration were identified and recommended. The results indicated the predictions of the model were highly reliable, with a total potential seagrasses distribution area was 3,296.47 km 2 in the study area. The distance from the shore, transparency, substrate type, SST, and nitrate concentration were identified as the dominant environmental variables. Seagrasses habitat suitability was high in study area when the distance from the shore was < 210 m, the SST was around 11 ~ 25°C, the substrate type was sandy with high mud content, the substrate particle size was around 35 ~ 330 µm, the transparency was around 0.7 ~ 1.5 m, and the nitrate concentration was< 6.4 mol·m -3 . This was the first study in which seagrasses were investigated and predicted in the Northern Chinese Seas, and their potential distribution and suitable habitat conditions were assessed. Our work will not only provide fundamental information for coastal seagrass ecosystem management, but also serve as a method to support the conservation and restoration of seagrasses.

Micromechanical analysis of the suction bucket-granular soil interactions under the pull action of anchor lines: Embedded length effect - Yu Peng; Yu Tan; Liming Qu (Ocean Engineering, 2024)

Dual positive charging sites for MIL-101 enhanced adsorption of toluene under high humidity conditions: Experimental and theoretical studies - Xinqi Luan; Syed Jalil Shah; Xin Yu; Ruimeng Wang; Jingyu Bao; Liming Liu; Jiguang Deng; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2024)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

From feedstock to digestion: Unraveling the impact of humic acid composition on anaerobic digestion - Yeqing Li; Shasha Yu; Xingru Yang; Yijing Feng; Liming Dong; Yi Zhang; Lu Feng; Mahmoud Mazarji; Junting Pan (Science of The Total Environment, 2023)

Machine learning aids solvothermal liquefaction of algal biomass: Prediction of nitrogen content and bio-oil yield - Oraléou Sangué Djandja; Ya-Qi Shan; Liming Fan; Yu Wu; Adekunlé Akim Salami; Xuebin Lu; Pei-Gao Duan; Shimin Kang (Fuel, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Microwave-assisted construction of MXene/MOF aerogel via N-metal bonds for efficient photodegradation of vapor acetone under high humidity - Xin Yu; Yang Hu; Xinqi Luan; Syed Jalil Shah; Liming Liu; Changhao Li; Yaofei Ren; Liqin Zhou; Jing Li; Jiguang Deng; Kungang Chai; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2023)

Designing hierarchically porous zero-valent iron via 3D printing to degrade organic pollutants by activating peroxymonosulfate using high-valent iron-oxo species - Sheng Guo; Meng Chen; Yu Wei; Liming You; Chao Cai; Qingsong Wei; Kun Zhou (Chemical Engineering Journal, 2023)

Modulation of tryptophan metabolism via AHR-IL22 pathway mediates the alleviation of DSS-induced colitis by chitooligosaccharides with different degrees of polymerization - Yu Wang; Xiaoguo Ji; Mengyao Zhao; Juan Li; Hao Yin; Jiayang Jin; Liming Zhao (Carbohydrate Polymers, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Composition and sources of suspended particles in the Pacific Arctic region - Xiaoguo Yu; Liming Ye; Yeping Bian; Yanguang Liu; Weiyan Zhang; Weiguo Wang; Xuying Yao; Jihao Zhu; Xiaobing Jin; Rong Wang (Marine Environmental Research, 2023)

The inhibition mechanism of nanoparticles-loading bilayer film on texture deterioration of refrigerated carp fillets from the perspective of protein changes and exudates - Liming Zhang; Dawei Yu; Yanshun Xu; Qixing Jiang; Dongxing Yu; Wenshui Xia (Food Chemistry, 2023)

Virus impacted community adaptation in oligotrophic groundwater environment revealed by Hi-C coupled metagenomic and viromic study - Zhanwen Cheng; Xiang Li; Alejandro Palomo; Qing Yang; Long Han; Ziqi Wu; Zengyi Li; Miao Zhang; Liming Chen; Bixi Zhao; Kaiqiang Yu; Chuanlun Zhang; et al. (Journal of Hazardous Materials, 2023)

Intelligent starch/chitosan-based film incorporated by anthocyanin-encapsulated amylopectin nanoparticles with high stability for food freshness monitoring - Luman Zheng; Liming Liu; Jiahao Yu; Mohamed A. Farag; Ping Shao (Food Control, 2023)

Phase equilibrium and evaporation process simulation for the lithium recovery from NaCl-LiCl-H2O system with high presence of organic NMP - Liming Lian; Xiaohua Song; Hang Chen; Jianguo Yu (Desalination, 2023)

Changes in quality and microbial diversity of refrigerated carp fillets treated by chitosan/zein bilayer film with curcumin/nisin-loaded pectin nanoparticles - Liming Zhang; Dawei Yu; Yanshun Xu; Qixing Jiang; Wenshui Xia; Dongxing Yu (Food Bioscience, 2023)

Enhancing wuyiencin productivity of Streptomyces albulus (CK15) by mutagenesis breeding with atmospheric and room temperature plasma - Yu Wah Thein; Liming Shi; Binghua Liu; Qiuhe Wei; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2023)

Integrated effect of bulk cations on nano-confined reactivity of clay-intercalated subnanoscale zero-valent iron in water-tetrahydrofuran mixtures - Kai Yu; Yanni Lv; Haowen Jiang; Huimin Li; Penghui Shao; Liming Yang; Hui Shi; Zhong Ren; Cun Liu; Xubiao Luo (Journal of Hazardous Materials, 2023)

Constructing a three-dimensional creep model for rocks and soils based on memory-dependent derivatives: A theoretical and experimental study - Liming Zhang; Deng Zhang; Zaiquan Wang; Yu Cong; Xiaoshan Wang (Computers and Geotechnics, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Transcriptional regulation of MbACO2-mediated ethylene synthesis during postharvest banana ripening - Yuqi Tang; Yan Yan; Weiwei Tie; Xiaoxue Ye; Liwang Zeng; Liming Zeng; Jinghao Yang; Biyu Xu; Meiying Li; Yu Wang; Zhengnan Xie; Zhiqiang Jin; et al. (Postharvest Biology and Technology, 2023)

A LiDAR biomass index-based approach for tree- and plot-level biomass mapping over forest farms using 3D point clouds - Liming Du; Yong Pang; Qiang Wang; Chengquan Huang; Yu Bai; Dongsheng Chen; Wei Lu; Dan Kong (Remote Sensing of Environment, 2023)

One-pot production of 5-methylfurfural (5-MF) and enhanced dewaterability of waste activated sludge by hydrothermal treatment with natural deep eutectic solvents (NADES): Experimental and theoretical studies - Xiaoping Liu; Yunbo Zhai; Zhixiang Xu; Yun Zhu; Yin Zhou; Zhexian Wang; Liming Liu; Fashen Liang; Wanying Ren; Yu Xie; Caiting Li; Min Xu (Chemical Engineering Journal, 2023)

Effects of four hormones on the mitigation of ovarian damage in tilapia (Oreochromis niloticus) after copper and cadmium exposure - Yijie Wu; Ting Huang; Xin Yan; Jun Xiao; Zhirui Ma; Liming Luo; Liting Chen; Jinling Cao; Zhanyang Tang; Xinxian Wei; Fuyan Chen; Yu Zhu; et al. (Aquatic Toxicology, 2023)

Spatial and temporal regulation of homogeneous nucleation and crystal growth for high-flux electrochemical water softening - Wenda Kang; Lujie Li; Liming Yan; Wei Mao; Xueqing Wang; Hongtao Yu; Chuanjun Ma (Water Research, 2023)

Genome-Wide Analysis of the Growth-Regulating Factor Family in Medicago truncatula - Hua Li; Taotao Qiu; Zhaosheng Zhou; Liqing Kang; Rongrong Chen; Liming Zeng; Hongyang Yu; Yihua Wang; Jianbo Song (Journal of Plant Growth Regulation, 2023)

Identification and expression of the CCO family during development, ripening and stress response in banana - Liming Zeng; Liwang Zeng; Yu Wang; Zhengnan Xie; Minhua Zhao; Jie Chen; Xiaoxue Ye; Weiwei Tie; Meiying Li; Sang Shang; Libo Tian; Jian Zeng; et al. (Genetica, 2023)

AUV-Based Side-Scan Sonar Real-Time Method for Underwater-Target Detection - Yulin Tang; Liming Wang; Shaohua Jin; Jianhu Zhao; Chao Huang; Yongcan Yu (Journal of Marine Science and Engineering, 2023)
The limitations of underwater acoustic communications mean that the side-scan sonar data of an autonomous underwater vehicle (AUV) cannot be transmitted back and processed in real time, which means that targets cannot be detected in real time. To address the problem, this paper proposes an autonomous underwater vehicle-based side-scan sonar real-time detection method for underwater targets. First, the paper describes the system and operation of real-time underwater-target detection by the side-scan sonar mounted on the autonomous underwater vehicle. Next, it proposes a real-time processing method for side-scan sonar data, method for constructing a deep-learning-based underwater-target detection model, and real-time method for underwater-target detection based on navigation strip images, which, together, solve the three key technical problems of real-time data processing, deep-learning-based detection model construction, and real-time target detection based on the autonomous underwater vehicle. Finally, through sea-based experiments, the effectiveness of the proposed methods is evaluated, providing a new solution for the autonomous underwater vehicle-based side-scan sonar real-time detection of underwater targets.

A zero-watermarking algorithm for vector geographic data based on feature invariants - Shuai Wang; Liming Zhang; Qihang Zhang; Yu Li (Earth Science Informatics, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Unraveling the impacts of Cu+-based treatments on sludge dewaterability: The overlooked role of Cu3+ - Xiaoping Liu; Yunbo Zhai; Zhixiang Xu; Liming Liu; Wanying Ren; Yu Xie; Caiting Li; Yun Zhu; Min Xu (Chemical Engineering Journal, 2023)

Electrostatic-modulated interfacial crosslinking and waterborne emulsion coating toward waterproof, breathable, and antifouling fibrous membranes - Jiatai Gu; Maorong Zheng; Tianxue Zhu; Ni Wang; Liming Wang; Jianyong Yu; Xiaohong Qin (Chemical Engineering Journal, 2023)

NIR-II fluorescence imaging-guided hepatocellular carcinoma treatment via IR-1061-acridine and lenvatinib co-loaded thermal-sensitive micelles and anti-PD-1 combinational therapy - Yan Du; Chunlei Shan; Yuchan You; Minjiang Chen; Luwen Zhu; Gaofeng Shu; Gang Han; Liming Wu; Jiansong Ji; Hong Yu; Yongzhong Du (Chemical Engineering Journal, 2023)

Human kidney organoids model of Esculentoside A nephrotoxicity to investigate the role of epithelial-mesenchymal transition via STING signaling - Shuyi Gu; Gaosong Wu; Dong Lu; Yu Wang; Liming Tang; Weidong Zhang (Toxicology Letters, 2023)

Electron-transfer-based peroxymonosulfate activation on defect-rich carbon nanotubes: Understanding the substituent effect on the selective oxidation of phenols - Shuiping Yu; Yanhua Peng; Penghui Shao; Yuanyue Wang; Youwen He; Wei Ren; Liming Yang; Hui Shi; Xubiao Luo (Journal of Hazardous Materials, 2023)

Effect of soil pH on thermally enhanced desorption of m-xylene by zero-valent iron particles under an electromagnetic field - Kai Yu; Xiuqiong Yang; Mao Wan; Haowen Jiang; Penghui Shao; Liming Yang; Hui Shi; Xubiao Luo (Journal of Hazardous Materials, 2023)

Pre-removing partial ammonium ions from the interlayer of ammonium vanadate with acid treating for quasi-solid-state flexible zinc ion batteries - Liming Chen; Haifeng Yue; Ziqiang Zhang; Yu Ma; Yuanming Wang; Ming Xu; Youyuan Huang; Guohui Yuan (Chemical Engineering Journal, 2023)

3D printed electrospun nanofiber-based pyramid-shaped solar vapor generator with hierarchical porous structure for efficient desalination - Ye Liu; Bin Luo; Huijie Liu; Mantang He; Rongwu Wang; Liming Wang; Zhenzhen Quan; Jianyong Yu; Xiaohong Qin (Chemical Engineering Journal, 2023)

Long non-coding RNA PRNCR1 promotes ovarian cancer cell proliferation, migration and invasion by targeting the miR-653-5p/ELF2 axis - Xing Qi; Dejun Chen; Weichang Yu; Liming Wang; Lu Liu; Xiaoling Tao (Molecular and Cellular Biochemistry, 2022)

Variation in carbon traits among Fraxinus mandshurica populations and allometric equations between carbon traits and growth traits - Xingtang Zhao; Nansong Liang; Liming He; Lei Yu; Yang Cao; Dean Xia; Ying Xiao; Guiqin Zhang; Fansuo Zeng; Yaguang Zhan (New Forests, 2021)

Identification of RNA helicases in Medicago truncatula and their expression patterns under abiotic stress - Jie Cheng; Songsong Zhou; Kun Yang; Hongyang Yu; Rongrong Chen; Liming Zeng; Hua Li; Yihua Wang; Jianbo Song (Physiology and Molecular Biology of Plants, 2021)

High-resolution genome-wide association study and genomic prediction for disease resistance and cold tolerance in wheat - Yunlong Pang; Yuye Wu; Chunxia Liu; Wenhui Li; Paul St. Amand; Amy Bernardo; Danfeng Wang; Lei Dong; Xiufang Yuan; Huirui Zhang; Meng Zhao; Linzhi Li; et al. (Theoretical and Applied Genetics, 2021)

Establishment of a micropropagation supporting technology for the Fraxinus mandshurica × Fraxinus sogdiana - Liming He; Yungang Xu; Fansuo Zeng; Hongmei Tian; Ying Xiao; Hualing Liu; Lei Yu; Yaguang Zhan (In Vitro Cellular & Developmental Biology - Plant, 2021)

Cardiac Na+-Ca2+ exchanger 1 (ncx1h) is critical for the ventricular cardiomyocyte formation via regulating the expression levels of gata4 and hand2 in zebrafish - Liming Chu; Huimin Yin; Lei Gao; Li Gao; Yu Xia; Chiyuan Zhang; Yi Chen; Tingxi Liu; Jijun Huang; Kenneth R. Boheler; Yong Zhou; Huang-Tian Yang (Science China Life Sciences, 2021)

Microstructural properties and compressive strength of lime or/and cement solidified silt: a multi-scale study - Shaoyun Pu; Zhiduo Zhu; Liming Zhao; Weilong Song; Yu Wan; Wangwen Huo; Hairong Wang; Kai Yao; Lele Hu (Bulletin of Engineering Geology and the Environment, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Ice sheet controls on fine-grained deposition at the southern Mendeleev Ridge since the penultimate interglacial - Liming Ye; Xiaoguo Yu; Weiyan Zhang; Rong Wang (Acta Oceanologica Sinica, 2020)

The Potential Vertical Distribution of Bigeye Tuna (Thunnus obesus) and Its Influence on the Spatial Distribution of CPUEs in the Tropical Atlantic Ocean - Shenglong Yang; Liming Song; Yu Zhang; Wei Fan; Bianbian Zhang; Yang Dai; Heng Zhang; Shengmao Zhang; Yumei Wu (Journal of Ocean University of China, 2020)

Plant abiotic stress response and nutrient use efficiency - Zhizhong Gong; Liming Xiong; Huazhong Shi; Shuhua Yang; Luis R. Herrera-Estrella; Guohua Xu; Dai-Yin Chao; Jingrui Li; Peng-Yun Wang; Feng Qin; Jijang Li; Yanglin Ding; et al. (Science China Life Sciences, 2020)

Genetic removal of the CH1 exon leads to the production of hypofunctional heavy chain-only IgG2a in rats - Zhenrong Li; Ming Zhang; Shunan Zheng; Yu Song; Xueqian Cheng; Di Yu; Lijuan Du; Liming Ren; Haitang Han; Yaofeng Zhao (Transgenic Research, 2020)

The Implementation of an Adjustable Afterload Module for Ex Situ Heart Perfusion - Bryan Gellner; Liming Xin; Roberto Vanin Pinto Ribeiro; Ved Bissoondath; Pengzhou Lu; Mitchell B. Adamson; Frank Yu; Emanuela Paradiso; Jean Zu; Craig A. Simmons; Mitesh V. Badiwala (Cardiovascular Engineering and Technology, 2020)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

Multimodal neuroimaging study reveals dissociable processes between structural and functional networks in patients with subacute intracerebral hemorrhage - Xiaobing Zhang; Xuebin Yu; Qingquan Bao; Liming Yang; Yu Sun; Peng Qi (Medical & Biological Engineering & Computing, 2019)

Growth, artificial seedling raising and cultivation of Sargassum confusum (Fucales, Phaeophyceae) inhabiting the coast of Shandong Peninsula, China - Jinhua Pan; Zhuangzhi Zhang; Shenhui Yu; Houwei Han; Xin Jiang; Liming Jiang; Guangjin Liang; Juan Sun; Xiaojie Li; Guanpin Yang (Journal of Applied Phycology, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Influence of Dentation Angle of Labyrinth Channel of Drip Emitters on Hydraulic and Anti‐Clogging Performance - Liming Yu; Na Li; Xiaogang Liu; Qiliang Yang; Zhangyan Li; Jun Long (Irrigation and Drainage, 2019)
The geometric parameters of labyrinth channels play an important role in the hydraulic and anti‐clogging performance of drip emitters. In this study , the flow fields, individual representative sands and sand groups in the labyrinth channel of emitters, with dentation angles of 90°, 60°, 45° and 30°, were firstly simulated using a computational fluid dynamics discrete element method (CFD–DEM) of coupling. Particle tracking velocimetry (PTV) was used to trace individual representative sands. The numerical results were verified with clear water hydraulic performance tests and muddy water anti‐clogging performance tests. The results suggest that the discharge coefficient and flow exponent declined when the dentation angle of the labyrinth channel was reduced. A large number of sand groups were observed to enter the vortex areas and move in a circular manner. The time it took for particles to pass through the labyrinth channel lengthened when the velocity decreased and as a result, the probability of emitter clogging increased. Therefore, by using a recommended angle range of 90° to 60° and a combined higher hydraulic performance level, emitters were less likely to clog. It was a novel approach to adopt a CFD–DEM coupling method to conduct numerical analysis of individual sand particles and sand groups in the investigation of emitter anti‐clogging issues. The findings will increase the design efficiency of flow channels and will save human and material resources. © 2018 John Wiley & Sons, Ltd.

Influence of Flushing Pressure before Irrigation on the Anti‐Clogging Performance of Labyrinth Channel Emitters - Liming Yu; Na Li; Qiliang Yang; Xiaogang Liu (Irrigation and Drainage, 2018)
This study aimed to investigate the influence of different pressures on the distribution of particle sizes of deposited sediments and discharged sands in the process of flushing, using cylindrical labyrinth channel emitters. Flushing was performed for 2 min before each irrigation under 0.15, 0.20, 0.25 and 0.30 MPa of pressure. The variation in flow discharge with irrigation times was measured after flushing, and a Malvern laser particle size analyser was employed to analyse the gradation of discharged sands. The results of this study suggested that irrigation time with normal outflow rate was remarkably extended and the anti‐clogging performance of emitters was obviously promoted by the increase in flushing pressures. Moreover, the emitters were sensitive to particles larger than 6.607 μm in diameter, which tended to be retained in the flow paths. In contrast, particles smaller than 6.607 μm in diameter flowed out of the labyrinth channel easily. Furthermore, the flushing pressure had a major impact on the larger particles of discharged sediments, whereas it had a minor effect on smaller particles. Increasing flushing pressures appropriately could effectively increase the passing rate of larger particles, thereby extending the lifespan of emitters. Therefore, it is advised to perform high‐pressure flushing for 2–3 min before each irrigation to prevent the clogging of emitters. Copyright © 2017 John Wiley & Sons, Ltd.

A national assessment of the effect of intensive agro-land use practices on nonpoint source pollution using emission scenarios and geo-spatial data - Dong Zhuo; Liming Liu; Huirong Yu; Chengcheng Yuan (Environmental Science and Pollution Research, 2018)

Equality testing for soil grid unit resolutions to polygon unit scales with DNDC modeling of regional SOC pools - Dongsheng Yu; Yue Pan; Haidong Zhang; Xiyang Wang; Yunlong Ni; Liming Zhang; Xuezheng Shi (Chinese Geographical Science, 2017)

Diallyl trisulfide ameliorates myocardial ischemia–reperfusion injury by reducing oxidative stress and endoplasmic reticulum stress-mediated apoptosis in type 1 diabetic rats: role of SIRT1 activation - Liming Yu; Shu Li; Xinlong Tang; Zhi Li; Jian Zhang; Xiaodong Xue; Jinsong Han; Yu Liu; Yuji Zhang; Yong Zhang; Yinli Xu; Yang Yang; et al. (Apoptosis, 2017)

Design, synthesis and biological activity of N-(3-substituted-phenyl)benzenesulfonamides as selective and reversible LSD1 inhibitors - Xiaoming Zha; Liming Wu; Siyuan Xu; Fangxia Zou; Jiayue Xi; Tianfang Ma; Rongfeng Liu; Yu-Chih Liu; Dawei Deng; Yueqing Gu; Jinpei Zhou; Fei Lan (Medicinal Chemistry Research, 2016)

Melatonin reduces PERK-eIF2α-ATF4-mediated endoplasmic reticulum stress during myocardial ischemia–reperfusion injury: role of RISK and SAFE pathways interaction - Liming Yu; Buying Li; Meng Zhang; Zhenxiao Jin; Weixun Duan; Guolong Zhao; Yang Yang; Zhenhua Liu; Wensheng Chen; Siwang Wang; Jian Yang; Dinghua Yi; et al. (Apoptosis, 2016)

Spatial Analysis of Cultural Heritage Landscapes in Rural China: Land Use Change and Its Risks for Conservation - Huirong Yu; Peter H. Verburg; Liming Liu; David A. Eitelberg (Environmental Management, 2016)

Model-based analysis of spatio-temporal changes in land use in Northeast China - Tian Xia; Wenbin Wu; Qingbo Zhou; Peter H. Verburg; Qiangyi Yu; Peng Yang; Liming Ye (Journal of Geographical Sciences, 2016)

Analysis of the reptile CD1 genes: evolutionary implications - Zhi Yang; Chunyan Wang; Tao Wang; Jianhui Bai; Yu Zhao; Xuhan Liu; Qingwei Ma; Xiaobing Wu; Ying Guo; Yaofeng Zhao; Liming Ren (Immunogenetics, 2015)

Protective effect of berberine against myocardial ischemia reperfusion injury: role of Notch1/Hes1-PTEN/Akt signaling - Liming Yu; Feijiang Li; Guolong Zhao; Yang Yang; Zhenxiao Jin; Mengen Zhai; Wenjun Yu; Lin Zhao; Wensheng Chen; Weixun Duan; Shiqiang Yu (Apoptosis, 2015)

The Effects of Oxidative Stress on the Compressive Damage Thresholds of C2C12 Mouse Myoblasts: Implications for Deep Tissue Injury - Yifei Yao; Zhitao Xiao; Singwan Wong; Yu-Chun Hsu; Truman Cheng; Chih-Chieh Chang; Liming Bian; Arthur F. T. Mak (Annals of Biomedical Engineering, 2015)

A microsatellite genetic linkage map of black rockfish (Sebastes schlegeli) - Guannan Chu; Liming Jiang; Yan He; Haiyang Yu; Zhigang Wang; Haibin Jiang; Quanqi Zhang (Journal of Ocean University of China, 2014)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Structural geology and tectonics in marine science: Perspectives in the research of deep sea and deep interior - Sanzhong Li; Chong Jin; Yanhui Suo; M. Santosh; Liming Dai; Xin Liu; Yun Ma; Xiaofei Wang; Bingkun Zhang; Shan Yu (Journal of Ocean University of China, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A functional variant of the collagen type III alpha1 gene modify risk of sporadic intracranial aneurysms - Jingzhou Chen; Yufang Zhu; Yuhua Jiang; Hui Yu; Kai Sun; Weihua Song; Liming Luan; Kejia Lou; Youxiang Li; Peng Jiang; Qi Pang; Rutai Hui (Human Genetics, 2012)

Bottom–up attention: pulsed PCA transform and pulsed cosine transform - Ying Yu; Bin Wang; Liming Zhang (Cognitive Neurodynamics, 2011)

Candida tropicalis: characterization of a strain capable of degrading high concentrations of phenol - Liming Wang; Yanwen Lin; Linyan Yang; Ping Yu; Zhixiong Xie; Yunbai Luo (Biotechnology Letters, 2011)

Analysis of new microsatellite markers developed from reported sequences of Japanese flounder Paralichthys olivaceus - Haiyang Yu; Liming Jiang; Wei Chen; Xubo Wang; Zhigang Wang; Quanqi Zhang (Journal of Ocean University of China, 2010)

Purification and in vitro cultivation of archaeocytes (stem cells) of the marine sponge Hymeniacidon perleve (Demospongiae) - Liming Sun; Yuefan Song; Yi Qu; Xingju Yu; Wei Zhang (Cell and Tissue Research, 2007)

Application of a new method to evaluate crop water stress index - Liming Wang; Guo Yu Qiu; Xiying Zhang; Suying Chen (Irrigation Science, 2005)